Introducing dental practice management in the undergraduate curriculum through an interprofessional module: experience from an Indian dental school - Sujir, Nanditha; Naik, Dilip G.; Mohammed, Ciraj Ali; Jain, Animesh; Uppoor, Ashita (Frontiers in Education, 2024)
Introduction: This study aimed to evaluate the effectiveness of a dental practice management education module developed through interprofessional collaboration.A dental practice management module was developed through need assessment, literature review, and interprofessional collaboration. The IP team included dental practitioners, dental educators, business expert, lawyer, bioethicist, engineer, and architects. Thirty interns were included in the study. Participants were assessed through pre-and post-test. Evaluation of the program was carried out by obtaining feedback from the students and dental practitioners who were invited to attend the program. The pre-and post-test results were compared by paired student ttest. p-value of < 0.01 was considered significant. The content of the feedback forms was subjected to qualitative and descriptive analysis.Results: Through the process of module preparation, pertinent competencies were identified and included in the program. There was a statistically significant increase in knowledge among students with respect to the domains included, as shown in the pre-post-test comparisons. The feedback obtained was positive. IP collaboration in module design and implementation was considered an important factor for dental practice management.Practice management education can be made effective through IP collaborations.